SKIP Silencing Decreased Disease Resistance Against Botrytis cinerea and Pseudomonas syringae pv. tomato DC3000 in Tomato - Zhang, Huijuan; Yin, Longfei; Song, Fengming; Jiang, Ming (Frontiers in Plant Science, 2020)
SKIP, a component of the spliceosome, is involved in numerous signaling pathways. However, there is no direct genetic evidence supporting the function of SKIP in defense responseg. In this paper, two SKIPs, namely, SlSKIP1a and SlSKIP1b, were analyzed in tomato. qRT-PCR analysis showed that the SlSKIP1b expression was triggered via Pseudomonas syringae pv. tomato (Pst) DC3000, Botrytis cinerea (B. cinerea), together with the defense-associated signals. In addition, the functions of SlSKIP1a and SlSKIP1b in disease resistance were completed analyzed in tomato through the virus-induced gene silencing (VIGS) technique. VIGS-mediated SlSKIP1b silencing led to increased accumulation of reactive oxygen species (ROS), along with the decreased expression of defense-related genes (DRGs) after pathogen infection, suggesting that it reduced B. cinerea and Pst DC3000 resistance. There was no significant difference in B. cinerea and Pst DC3000 resistance in TRV-SlSKIP1a-infiltrated plants compared with the TRV-GUS-silencing counterparts. As suggested by the above findings, SlSKIP1b plays a vital role in disease resistance against pathogens possibly by regulating the accumulation of ROS as well as the expression of DRGs.